KONTESTASI GELAR ADAT â€œSUTTANâ€ DALAM PANGGUNG POLITIK LAMPUNG - Valentina, Annissa (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2018)
This article examines the shifting of the meaning of the title of adat where thereis a dualism of the function of the title of adat when traditional leaders enter the political world or vice versa, politicians who get customary titles. The highest customary titles such as